2016
DOI: 10.3892/etm.2016.3091
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the effects of different doses of recombinant human growth hormone on children with growth hormone deficiency

Abstract: The aim of the present study was to examine the effects of different doses of recombinant human growth hormone (rhGH) on children with growth hormone deficiency (GHD) and on thyroid and glucose metabolism to identify more reasonable therapeutic doses of growth hormone (GH) for the treatment of this condition. In total, 60 prepubertal patients with GHD were randomly divided into the high-dose and low-dose groups (n=30 per group). The groups were treated with 0.1 or 0.05 U/kg for 6 months, respectively. The foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
1
7
0
2
Order By: Relevance
“…Fasting glucose is undoubtedly the parameter mostly used to evaluate glucose metabolism in almost all studies (21/24; 87.5%). In a recent study, Xue et al reported a significant increase in fasting glucose in 60 children during 6 months of GHT, although in half of the patients a high GH dose (0.1 U/kg) was used ( 72 ). Similar results have been shown by Chen et al in 60 children after 12 months of GHT, regardless of the GH dose used ( 68 ) and these data have been confirmed by four other studies ( 60 , 62 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fasting glucose is undoubtedly the parameter mostly used to evaluate glucose metabolism in almost all studies (21/24; 87.5%). In a recent study, Xue et al reported a significant increase in fasting glucose in 60 children during 6 months of GHT, although in half of the patients a high GH dose (0.1 U/kg) was used ( 72 ). Similar results have been shown by Chen et al in 60 children after 12 months of GHT, regardless of the GH dose used ( 68 ) and these data have been confirmed by four other studies ( 60 , 62 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data from the main registries on children treated with rhGH (5,6) suggest that this therapy may accelerate the onset of type 2 diabetes mellitus in predisposed patients, with a prevalence of 0.36% of abnormal glucose metabolism and a six-fold increase in the incidence of type 2 diabetes. Several other studies have investigated the effects of rhGH therapy on glucose metabolism in children (17,18,19,20,21,22). Nevertheless, as highlighted in a recent systematic review (8), only in relatively few studies glucose metabolism abnormalities were the main outcome.…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSION Data from the main registries on children treated with rhGH (5,6) suggest that this therapy may accelerate the onset of type 2 diabetes mellitus in predisposed patients, with a prevalence of 0.36% of abnormal glucose metabolism and a six-fold increase in the incidence of type 2 diabetes. Several other studies have investigated the effects of rhGH therapy on glucose metabolism in children (17)(18)(19)(20)(21)(22). Nevertheless, as highlighted in a recent systematic review (8), only in relatively few studies glucose metabolism abnormalities were the main outcome.…”
Section: Evaluation Of Glucose Metabolismmentioning
confidence: 99%